Zygomatic complex fractures in a Nigerian tertiary hospital: An update on the pattern of presentation and care - Obimakinde OS; Olajuyin OA; Akinbade AO; Ojo KO; Ibidun CO; Ogunsakin OT (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2022)
Aim:  The Zygomatic complex [ZMC], being one of the most commonly fractured bones in the facial skeleton, is largely underreported in the literature. This study was designed to evaluate the pattern of fractures, symptomatology, and treatment modalities at our institution.  Materials and methods: Information on patients' sociodemographics, the pattern of fractures, symptomatology, radiologic diagnosis, and treatment modalities were accessed from patients' records on our trauma register. Data collected was analyzed with SPSS 20 and the level of significance was set at p < 0.05. Results: A total of 105 patients aged 19-66 years had ZMC fractures during the study period. A male preponderance was observed [M: F  =  3.8:1] and road traffic crashes [RTC] accounted for the majority of fractures [79.0%]. There was a statistically significant relationship between RTC and fractures among the age groups [X2 = 33.61, df = 5, p  =  0.001]. Fractures at the zygomatico-frontal [ZF] and in combination with zygomaticomaxillary [ZM] sutures were the commonest finding on imaging [39.1% % 28.6% respectively]. Subconjunctival and circumorbital ecchymosis [92.4% and 91.4% respectively] were the commonest symptomatology. Eighty four patients (80 %) were managed via surgical intervention and the most commonly employed surgical modality was mini plates [1.0mm] fixation across either ZF [n  =  33, 39.3%] or ZM [n  =  21, 25.0%] suture lines. Conclusion: This study revealed that RTC remains a major aetiology of ZMC fractures and mini plate ostheosynthesis was the mainstay of surgical management. Enforcement of road safety regulations on speed and the use of protective measures by road users is imperative.